Impacts of phosphite treatment on Phytophthora community assemblages and inoculum abundances in Phytophthora-infected forest soil - Shannon Hunter; Nick Waipara; Bruce Burns; Peter Scott; Nari Williams (Trees, Forests and People)
Phytophthora are causing declines in forest tree species worldwide and the chemical control treatment, phosphite, is the only treatment consistently shown to provide some protection to natural ecosystems from Phytophthora diseases. Phosphite inhibits Phytophthora growth and sporulation whilst boosting defence responses in the plant host. It is unclear, however, the extent of the impact of phosphite on Phytophthora species assemblages and inoculum abundances in soil around trees following treatment within natural ecosystems. In New Zealand, kauri (Agathis australis), an endemic and threatened foundation species, suffers from a dieback disease primarily caused by Phytophthora agathidicida. Phosphite is applied by trunk injection to kauri and has been shown to improve resin ‘bleed’ symptoms from basal trunk lesions and to promote recovery of thinned canopies. Phytophthora community and inoculum abundance were investigated in response to phosphite treatments at two field sites (Huia and Waitoki) in infected kauri stands in Auckland, New Zealand. At Huia, soil sampling and tree health surveying were conducted in November 2023 on trees treated with phosphite in 2012 as part of an earlier study. At Waitoki, the response to phosphite treatment was monitored 6 and 18 months following treatment. Phytophthora species were detected using soil baiting and metabarcoding of Environmental DNA (eDNA) from soil and quantified with qPCR of root and soil DNA. Three species were detected with soil baiting (P. agathidicida, P. cinnamomi, and P. multivora) and two additional species with metabarcoding (P. pseudocryptogea, and an unknown clade 7 species similar to P. europaea). Phytophthora cinnamomi was the most abundant species, followed by P. agathidicida. Both species were more likely to occur together than by chance alone and were associated with declining tree health. The P. europaea-like species was in approximately 50 % of the samples and was less likely to occur in roots with poorer health, or in association with P. agathidicida. The abundance of P. agathidicida inoculum was lower in the soil around the phosphite-treated trees than around the untreated control trees 1.5 years after treatment at Waitoki. Phosphite halted the lateral expansion of basal resin bleeds, and resin viscosity was reduced. Not only did phosphite treatments improve kauri dieback symptoms, but the phosphite treatments potentially had a direct impact on the epidemiology of the disease by reducing inoculum load around treated trees, with direct implications for disease management as an effective way to protect uninfected areas and minimise the spread of inoculum from infested zones.